MENINGKATKAN HASIL DAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI MODEL PROBLEM BASED LEARNING - Syaadah Aisyah Nurjanah; Asih Aryani (Balai Diklat Keagamaan Bandung, 2020)
AbstractThis research was originated from students’ low learning outcomes and motivation in Mathematics Class VII-A MTs YI Rajamandala. Their average score is still below minimum criteria of mastery learning. The research objective is to improve mathematics learning outcomes on the Topic of One Variable Linear Equations and Inequalities. This research is a classroom action research conducted in 2 cycles, consisting of planning, acting, observing and reflecting. Data were analyzed using descriptive analysis. Based on the discussion and data analysis, it is concluded that; a) the initial conditions for students’ activeness and learning outcomes before Problem Based Learning model applied was low, b) there is an increase in student learning outcomes, in form of values and changes in learning motivation which consist of: seriously showing interest, trying hard to be available, and continuing to work until the task is completed, c) there is an increase in both activeness and learning outcomes after using Problem Based Learning model as much as 13%, from an initial average of 65% to 78% at the end of the cycle. Keywords: Learning Achievement; Learning Motivation; Problem Based Learning